Analisis Efisiensi Termal PLTGU Muara Karang Blok 2 Menggunakan Sankey Diagram pada Beban 135 MW - Muhammad Ridwan (TURBO [Tulisan Riset Berbasis Online], 2025)
The growing demand for electricity requires a proportional increase in power generation to ensure a stable supply for both public and industrial needs. To maintain this stability, Gas and Steam Power Plants (PLTGU) must operate in optimal condition. Thermal efficiency plays a crucial role in determining the plant’s ability to generate electricity effectively. This study aims to analyze the thermal efficiency of PLTGU UP Muara Karang Block 2 at a 135 MW load using the Sankey Diagram approach. This method provides a comprehensive visualization of energy flow and system efficiency. The analysis is based on the First Law of Thermodynamics, focusing on key components such as the compressor, gas turbine, combustor, and other essential elements. The results show an increase in thermal efficiency from 84.92% to 86.40% after an overhaul. This improvement reflects better heat distribution to the main components, indicating more optimal energy conversion. Additionally, the reduction in heat loss signifies an overall enhancement in energy efficiency.